EVALUATING THE RELATIONSHIP BETWEEN ILLNESS PERCEPTION, EXPECTATIONS REGARDING AGING, HEALTH LOCUS OF CONTROL, AND MEDICATION ADHERENCE AMONG OLDER ADULTS WITH CHRONIC CONDITIONS - (:unkn) unknown (My University, 2025)
Background: Medication adherence among older adults with chronic conditions is a critical determinant of health outcomes. However, adherence behaviors are influenced by multiple psychosocial factors. This study examined the relationship between illness perception, expectations regarding aging, health locus of control, and medication adherence among older adults with chronic conditions in Jordan. Methods: A cross-sectional correlational study was conducted with 120 older adults (≥65 years) diagnosed with at least one chronic condition and receiving prescription medication. Participants were recruited from outpatient clinics at King Abdullah University Hospital in Irbid, Jordan, using convenience sampling. Data were collected via self-report and using validated Arabic versions of the Medication Adherence Report Scale (MARS-5), Brief Illness Perception Questionnaire (BIPQ), Expectations Regarding Aging Survey (ERA-12), and Multidimensional Health Locus of Control (MHLC) Form A. The data was analyzed by descriptive statistics, non-parametric tests, Spearman correlations, and multiple linear regression.Results: Participants reported moderate to high medication adherence (M = 21.84, SD = 3.16). Illness perception was negatively associated with adherence (β = –0.221, p = .024), while belief in powerful others (e.g., healthcare providers) positively predicted adherence (β = 0.286, p = .008). Internal and chance health locus of control, expectations regarding aging, and demographic variables were not significantly associated with adherence. The final regression model explained 13.1% of the variance in adherence scores (Adjusted R² = .092). Conclusions: Illness-related beliefs and trust in healthcare providers are significant predictors of medication adherence among older adults in Jordan. Interventions aiming to enhance adherence should focus on addressing maladaptive illness perceptions and fostering strong patient-provider relationships. Sociodemographic factors and general aging expectations were not predictive, suggesting that adherence interventions should prioritize psychosocial rather than demographic targeting.
Keywords: Gerontology; Health sciences; Health care management; chronic conditions; Health Locus of Control; Illness Perception; Jordan; Medication adherence; older adults